Predictors of oral pre-exposure prophylaxis (PrEP) uptake among individuals in a HIV vaccine preparedness cohort in Masaka, Uganda. Issue 44 (5th November 2021) - Kusemererwa, Sylvia; Kansiime, Sheila; Mutonyi, Gertrude; Namirembe, Aeron; Katana, Safina; Kitonsa, Jonathan; Kakande, Ayoub; Okello, Joseph Mugisha; Kaleebu, Pontiano; Ruzagira, Eugene
Abstract : Abstract: Oral pre-exposure prophylaxis (PrEP) significantly reduces human immunodeficiency virus (HIV) acquisition risk. However, data on predictors of PrEP uptake in sub-Saharan Africa are limited. We assessed predictors of PrEP uptake among HIV-uninfected high risk individuals enrolled in a HIV vaccine preparedness study in Masaka, Uganda. Between July 2018 and October 2020, we recruited adults (18–40 years) from sex work hotspots along the trans-African highway and Lake Victoria fishing communities. We collected baseline data on socio-demographics and PrEP awareness, and provided HIV counselling and testing, information on PrEP, and PrEP referrals at quarterly visits. Urine pregnancy tests (women) and data collection on sexual risk behaviour and PrEP uptake were performed every 6 months. We analysed PrEP uptake among participants who had completed 6 months of follow-up. Of the 588 cohort participants, 362 (62%) were included in this analysis. Of these, 176 (49%) were female, 181 (50%) were aged ⩽24 years, 104 (29%) worked in sex work hotspots, 74 (20%) were fisher folk. Only 75 (21%) participants initiated PrEP. Predictors of PrEP uptake included having ≥6 sex partners (adjusted odds ratio [aOR] = 2.29; 95% confidence interval [CI] 1.26–4.17), engaging in transactional sex (aOR = 2.23; 95% CI 0.95–5.20), and residence in a nonfishing community (aOR = 2.40; 95% CI 1.14–5.08). The commonest reasons for not starting PrEP were pill burden (38%) and needing more time to decide (27%). PrEP uptake was low and associated with HIV risk indicators in this cohort. Interventions are needed to improve access to PrEP especially in fishing communities.